Abnormal returns or mismeasured risk? Network effects and risk spillover in stock returns - Arnab Bhattacharjee; Sudipto Roy (Journal of Risk and Financial Management, 2019)
Recent event study literature has highlighted abnormal stock returns, particularly in short event windows. A common explanation is the cross-correlation of stock returns that are often enhanced during periods of sharp market movements. This suggests the misspecification of the underlying factor model, typically the Fama-French model. By drawing upon recent panel data literature with cross-section dependence, we argue that the Fame-French factor model can be enriched by allowing explicitly for network effects between stock returns. We show that recent empirical work is consistent with the above interpretation, and we advance some hypotheses along which new structural models for stock returns may be developed. Applied to data on stock returns for the 30 Dow Jones Industrial Average (DJIA) stocks, our framework provides exciting new insights.
Keywords: 330; Fama-French factor model; market microstructure; trading behavior; panel data factor model; social network model; risk spillover; abnormal returns